Poverty Rate VS TPACK Mastery: A Study of Physical Education Teachers Candidate from Low-Income Families - Karisman, Vicki Ahmad; Wahyudi, Rizky (Physical Activity Journal (PAJU), 2024)
This study examined the mastery of Technological Pedagogical Content Knowledge (TPACK) for Physical Education (PE) teachers candidates from low-income families. Candidate teachers from low-income families have less access to information technology, so this research examines the mastery level of TPACK among physical education teachers from low-income families. This research used a quantitative approach with a survey method. The survey instrument utilized a TPACK survey to assess the mastery of technology in the teaching and learning process. The participants involved in this study were 146 students who received the Kartu Indonesia Pintar (KIP) Scholarship (government scholarship) and came from low-income families. The results showed that the candidate teachers were included in a Good TPACK skills category. This result indicates that low income does not affect the ability to master TPACK skills. This study rejects the notion that low-income students have low mastery of technology.